2021
DOI: 10.2460/javma.258.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Current attitudes of veterinarians and producers regarding the use of local and systemic analgesia in beef and dairy cattle in the United States

Abstract: OBJECTIVE To survey cattle producers and veterinarians about the use of analgesia on US cattle operations. SAMPLE 1,187 members of the following database, electronic mailing lists, and social media groups: FarmProgress master file, American Association of Bovine Practitioners, Academy of Veterinary Consultants, National Milk Producers Federation Farm Evaluators, Dairy Moms Facebook group, and Dairy Girl Network Facebook group. PROCEDURES An online survey was developed to gather information about the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Time is often indicated as a major obstacle limiting the use of analgesic agents in cattle, as also discussed recently by Johnstone et al (2021). In the present study, the time to recumbency did not differ between calves sedated with levomethadone and xylazine (0.1 mg kg −1 ) and calves given only xylazine (0.2 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 69%
“…Time is often indicated as a major obstacle limiting the use of analgesic agents in cattle, as also discussed recently by Johnstone et al (2021). In the present study, the time to recumbency did not differ between calves sedated with levomethadone and xylazine (0.1 mg kg −1 ) and calves given only xylazine (0.2 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 69%
“…Additional outcomes are reported in Bergamasco et al [ 21 ], a companion paper that can be referred to for further information. Despite the fact that surgical castration is a painful procedure having both acute and chronic impacts, the use of pain control is not routinely practiced in the United States [ 1 , 2 ]. Surveys of producers and/or veterinarians exploring pain mitigation use for various management procedures including castration have demonstrated that analgesia use increases with cattle age [ 2 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that surgical castration is a painful procedure having both acute and chronic impacts, the use of pain control is not routinely practiced in the United States [ 1 , 2 ]. Surveys of producers and/or veterinarians exploring pain mitigation use for various management procedures including castration have demonstrated that analgesia use increases with cattle age [ 2 , 25 ]. Industry guidelines for castration procedures suggest performing the procedure at the youngest age possible to reduce stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations